2000
DOI: 10.1055/s-0037-1613752
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Procoagulant-anticoagulant Balance during Hormone Replacement Therapy?

Abstract: SummaryIn this randomised, placebo-controlled 12-week study, sixty healthy postmenopausal women received either placebo (N = 16) or daily 2 mg micronised oestradiol, either unopposed (N = 16, E2 group) or combined with a progestagen for 14 days of each cycle (N = 28, E2+P group).As compared to placebo, plasma levels of AT III were reduced only in the E2 group (∼28%), plasma levels of protein C decreased only in the E2+P group (∼4%) and plasma levels of protein S decreased in both the E2 and E2+P group (∼21%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 42 publications
5
76
0
Order By: Relevance
“…Protein S is present in plasma in two forms, as approximately 60% is bound to C4b-binding protein, while the remaining part circulates in free form. Apparently, HRT does not alter the concentration of free protein S in plasma 9,13,15,21,22 , while the total protein S concentration is reduced 11,13,22 . However, HRT reduces the concentration of C4b-binding protein 23 , and this can explain why HRT reduces the total concentration of protein S. Free protein S is an important co-factor in the activated protein C-induced degradation of factor Va, while bound protein S does not possess this function.…”
Section: Discussionmentioning
confidence: 89%
“…Protein S is present in plasma in two forms, as approximately 60% is bound to C4b-binding protein, while the remaining part circulates in free form. Apparently, HRT does not alter the concentration of free protein S in plasma 9,13,15,21,22 , while the total protein S concentration is reduced 11,13,22 . However, HRT reduces the concentration of C4b-binding protein 23 , and this can explain why HRT reduces the total concentration of protein S. Free protein S is an important co-factor in the activated protein C-induced degradation of factor Va, while bound protein S does not possess this function.…”
Section: Discussionmentioning
confidence: 89%
“…34 Moreover, several trials have failed to show any changes in levels of hemostatic parameters between progestogen subgroups. [35][36][37][38] Nevertheless, recent data suggested that trimegestone, a norpregnane derivative, had a stronger effect on fibrinolysis inhibition as compared to dydrogesterone. 39 Thus, whether or not progestogens have differential effects on hemostasis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the norpregnane derivatives, one randomized trial failed to show any changes in hemostatic variables among women receiving oral estrogen combined with nomegestrol acetate. 33 Among women recruited from the Project Aging Women, van Baal et al 34 and Post et al 35 have studied the effect of trimegestone (a norpregnane derivative), dydrogesterone, or both combined with oral estrogen therapy on hemostatic variables. Deleterious effects of oral estrogen therapy on coagulation without significant differences between all progestogen subgroups were found.…”
Section: Discussionmentioning
confidence: 99%